Determinan Fee Audit Eksternal Perusahaan Property dan Real Estate Terdaftar di BEI Periode 2018-2022 - Martini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In Indonesia, information regarding the amount of audit fees that companies will pay to public accountants is still difficult to find. Determination of audit compensation currently still depends on the agreement between the company and the Public Accounting Firm. This research aims to analyze the influence of Financial Distress, KAP Reputation, Company Complexity and Company Profitability on External Audit Fees. The data used in this research was obtained through the official website of the Indonesia Stock Exchange (BEI). The population in this research is all property and real estate sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022, totaling 85 companies and after sampling, 40 samples were obtained. The sample in this research used the Purposive Sampling method. The analysis technique used in this research is multiple linear regression. The results of this research show that financial distress, KAP reputation and complexity have no effect on external audit fees. Meanwhile, profitability has an influence on external audit fees.